2013
DOI: 10.1158/0008-5472.can-13-1794
|View full text |Cite|
|
Sign up to set email alerts
|

CD95L Cell Surface Cleavage Triggers a Prometastatic Signaling Pathway in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancers (TNBC) lacking estrogen and progesterone receptors and HER2 amplification have a relatively high risk of metastatic dissemination, but the mechanistic basis for this risk is not understood. Here, we report that serum levels of CD95 ligand (CD95L) are higher in patients with TNBC than in other patients with breast cancer. Metalloprotease-mediated cleavage of CD95L expressed by endothelial cells surrounding tumors generates a gradient that promotes cell motility due to the formatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(131 citation statements)
references
References 34 publications
8
120
2
1
Order By: Relevance
“…It is worth mentioning that soluble trimeric CD95L, which as discussed above, is practically unable at reasonable concentrations to stimulate caspase 8 activation and apoptosis, also fails to stimulate robust lipid raft translocation of CD95 (Lang et al, 2012). In view of the ability of sCD95L to induce a FADD-and caspase 8-independent signaling complex (Kleber et al, 2008;Malleter et al, 2013), it will be interesting to see in future studies whether insults that modify CD95 distribution between lipid rafts and the surrounding bulk plasma membrane affect the balance between sCD95L-induced FADD-independent and memCD95L-induced FADD-dependent signaling complexes. In accordance with the fact that a variety of factors and cellular stressor trigger CD95L-independent redistribution of CD95 into lipid raft (Table 1), we recently demonstrated by help of cells co-expressing chimeric CD40-CD95 receptors and endogenous CD95 that caspase 8-activating CD95 species trigger the lipid raft translocation of unliganded CD95 molecules as well (Lang et al, 2012).…”
Section: The Role Of Lipid Rafts In Apoptotic Cd95 Signalingmentioning
confidence: 94%
See 2 more Smart Citations
“…It is worth mentioning that soluble trimeric CD95L, which as discussed above, is practically unable at reasonable concentrations to stimulate caspase 8 activation and apoptosis, also fails to stimulate robust lipid raft translocation of CD95 (Lang et al, 2012). In view of the ability of sCD95L to induce a FADD-and caspase 8-independent signaling complex (Kleber et al, 2008;Malleter et al, 2013), it will be interesting to see in future studies whether insults that modify CD95 distribution between lipid rafts and the surrounding bulk plasma membrane affect the balance between sCD95L-induced FADD-independent and memCD95L-induced FADD-dependent signaling complexes. In accordance with the fact that a variety of factors and cellular stressor trigger CD95L-independent redistribution of CD95 into lipid raft (Table 1), we recently demonstrated by help of cells co-expressing chimeric CD40-CD95 receptors and endogenous CD95 that caspase 8-activating CD95 species trigger the lipid raft translocation of unliganded CD95 molecules as well (Lang et al, 2012).…”
Section: The Role Of Lipid Rafts In Apoptotic Cd95 Signalingmentioning
confidence: 94%
“…Soluble CD95L-induced activation of NFκB is strongly enhanced by oligomerization and resembles in this respect CD95L-induced FADD-and caspase-8-mediated apoptosis and CD95L-induced FADD-and RIP1-mediated necroptosis. CD95-induced activation of the MAP kinase pathway as well as stimulation of PI3K/Akt pathway-activating tyrosine kinases and promotion of cell migration, however, occur at least in some cellular models independently of the CD95 DD and the recruitment of FADD (Desbarats et al, 2003;Kleber et al, 2008;Malleter et al, 2013). Noteworthy, the cellular CD95 responses triggered by these pathways are already efficiently stimulated by sCD95L, and this also pertains to a study in which CD95-induced cell migration required the DD of the molecule (Desbarats et al, 2003;Kleber et al, 2008;Tauzin et al, 2011;Malleter et al, 2013).…”
Section: Cd95-associated Signaling Pathways Differ In Their Requiremementioning
confidence: 97%
See 1 more Smart Citation
“…metalloprotease-cleaved CD95L implements non-apoptotic signals in cells expressing two wild-type alleles of CD95 [48,50,116,117] (further discussed in 3.6.2). In summary, because the characterization of CD95/CD95L biological roles has been carried out mainly by considering the default of apoptosis in ALPS type Ia patients and mouse models, we believe it is important to carefully reconsider these conclusions by integrating the notion that exposure of these cells to CD95L will also lead to a chronic activation of non-apoptotic signaling pathways [99].…”
Section: Mouse Modelsmentioning
confidence: 99%
“…We recently showed that CD95 implements the PI3K signaling pathway by recruiting EGFR. This CD95-dependent EGFR activation relies on the recruitment of the NADPH oxidase 3 (Nox3), the production of reactive oxygen species, which in turn activate the src kinase c-yes [117]. In triple-negative breast cancer cells exposed to metalloprotease-cleaved CD95L, c-yes activation is instrumental in forming an EGFR-containing MISC, and this receptor tyrosine kinase (RTK) orchestrates the activation of PI3K…”
Section: (At Least) Two Different Ligands and Two Different Signalsmentioning
confidence: 99%